2012
DOI: 10.1242/jeb.073429
|View full text |Cite
|
Sign up to set email alerts
|

Light Interference (LI) as a possible stressor altering HSP70 and its gene expression levels in brain and liver tissues of Golden Spiny Mice

Abstract: SUMMARYLight at night and light interference (LI) disrupt the natural light:dark cycle, causing alterations at physiological and molecular levels, partly by suppressing melatonin (MLT) secretion at night. Heat shock proteins (HSPs) can be activated in response to environmental changes. We assessed changes in gene expression and protein level of HSP70 in brain and hepatic tissues of golden spiny mice (Acomys russatus) acclimated to LI for two (SLI), seven (MLI) and 21 nights (LLI). The effect of MLT treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…These span studies of gene expression (e.g. [41,42]), physiology (e.g. [43][44][45][46]), foraging [24,[47][48][49][50], daily movements [51][52][53][54][55], migratory behaviour (e.g.…”
Section: Individual Organismsmentioning
confidence: 99%
“…These span studies of gene expression (e.g. [41,42]), physiology (e.g. [43][44][45][46]), foraging [24,[47][48][49][50], daily movements [51][52][53][54][55], migratory behaviour (e.g.…”
Section: Individual Organismsmentioning
confidence: 99%
“…In turn this can result in changes in expression of heat shock proteins, cortisol production and immune function, and increased risk of cancer (e.g. Dauchy et al 1997; Bedrosian et al 2011, 2013; Ashkenazi and Haim 2012; Schwimmer et al 2014). This suggests that wild populations may also experience significant health impacts from ALAN.…”
Section: Effects On Terrestrial Ecosystemsmentioning
confidence: 99%
“…According to the second potential impact mechanism, humans, being involved in night-time activities enabled by ALAN, may suffer from daily rhythms disruption, leading to increased susceptibility to various diseases, including BC (Haim & Portnov, 2013;Navara & Nelson, 2007;Stevens & Rea, 2001). According to the third potential impact mechanism, ALAN may work as a general stressor and endocrine disruptor, especially when changes in nighttime light intensity are sudden and unexpected (Ashkenazi & Haim, 2012;Haim & Portnov, 2013;Navara & Nelson, 2007;Zubidat et al, 2007). In a recent review it was also suggested that MLT is a mediator between the environment and epigenome (Haim & Zubidat, 2015), supporting the results obtained earlier by Schwimmer et al (2014).…”
Section: Introductionmentioning
confidence: 64%